Winyann and Affective Performance among Female Thai Flight Attendants - Arratee Ayuttacorn (2018)
© 2016 The Australian National University. Building on Hochschild's concept of emotional work and Sarah Ahmed's theory of affective economy, this paper examines the ways in which female Thai flight attendants mobilise winyann—a Buddhist notion of soul, but applied to airline professionalism—to perform their duties and manage work-related crises. Ethnographic evidence shows that Buddhist concepts of soul and suffering are used to transcend difficult situations in the air, paradoxically creating value for the corporation while still allowing women to experience personal integrity through embodied performances of affect in their professional lives.